INDIA'S SECURITY THREATS FROM CHINESE MILITARY FUNDING AND ECONOMIC DEVELOPMENT IN SOUTH ASIA - My Hai Loc, Tran (UI Scholars Hub, 2023)
Since gaining independence in 1947, India's population, expansive land size, robust economic position, and historical and cultural ties have enabled it to dominate South Asian neighbours with comparatively less developed economies and weaker military strength. Since Narendra Modi assumed office as the Prime Minister of India in 2014, the “Neighbourhood First” policy was coined to enhance India's influence in South Asia, creating a favourable environment for its ascent as a global power. However, China's increasing military presence and influence in South Asia through financial and military support to neighbouring countries have disrupted the region's security architecture. This article uses qualitative methodologies to examine India's security threats from China's military and economic support to South Asian countries. The paper finds that South Asia holds a crucial and prioritised position in the foreign policies of both India and China. The strategic competition between India and China in the South Asian region has had and continues to impact the countries in the area significantly. With financial and military support, China is gradually shaping its influence in South Asia, posing a security threat that could isolate India in the Indian Ocean region. It concludes that China's attempts to contain India in the region led India to enhance military cooperation and strengthen its defence partnership with significant countries in the Indo-Pacific region to limit the threats from China.